2014
DOI: 10.1007/s10495-014-1080-2
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis 38-kDa antigen induces endoplasmic reticulum stress-mediated apoptosis via toll-like receptor 2/4

Abstract: Endoplasmic reticulum (ER) stress responses play critical roles in the pathogenesis of tuberculosis. To investigate the regulatory role of the ER stress response in 38-kDa antigen-induced apoptosis, we examined the relationship between the ER stress response and apoptosis in bone marrow-derived macrophages (BMDMs) stimulated with Mycobacterium tuberculosis antigen (38-kDa Ag). The expression of ER molecular chaperones, including C/EBP homologous protein (CHOP), glucose-regulated protein (Bip) and phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 45 publications
1
55
0
Order By: Relevance
“…Other modulated gene expression patterns have been noted (e.g. increased expression of Irg1 52, Ltb4r 47, Ctla4 , Pdcd1 (PD-1), Cd274 (PD-L1), Lag3 , Socs3 , Zc3h12a (MCPIP)53; decreased expression of Pparg ) (Fig. 2E,G; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Other modulated gene expression patterns have been noted (e.g. increased expression of Irg1 52, Ltb4r 47, Ctla4 , Pdcd1 (PD-1), Cd274 (PD-L1), Lag3 , Socs3 , Zc3h12a (MCPIP)53; decreased expression of Pparg ) (Fig. 2E,G; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 86%
“…2D,G; Supplementary Fig. 4A,B) following anti-TNFα treatment, both induced by M. tuberculosis 38-kDa antigen in vitro 53, and indicative of monocyte recruitment and macrophage M2 polarization62, respectively. MCPIP1, recently shown to negatively regulate IL-17-mediated signaling and inflammation63, may be one of several immunoregulatory factors engaged in containing infection and limiting host pathology.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…NF-κB activation is not only associated with Par-4 production, but also with infection control1415. Importantly, ROS induce ER stress and lead to NF-κB activation during mycobacterial infection2324. These data suggest that mycobacteria-mediated ROS generation is important for inducing Par-4 mediated apoptosis through ER stress activation.…”
Section: Discussionmentioning
confidence: 92%
“…Mtb -induced GRP78 raised the possibility that it binds to Par-4, and GRP78/Par-4 complex is localized at plasma membrane of macrophage. Previously, we suggested that ER stress induced by infection or antigen stimulation of mycobacteria is important to regulate apoptotic cell death112324. GRP78 localized to the plasma membrane acts as a receptor for extracellular Par-4 leading to activation of apoptosis via mitochondrial release of cytochrome C and caspase activation25.…”
Section: Discussionmentioning
confidence: 99%